Back Cover. Issue 2 (18th January 2020) - Unknown
Abstract : The back cover picture shows an efficient organic ligand‐free heterogeneous catalytic system for hydroformylation of olefins with simple Rh particles as the catalyst. The Rh black catalyst showed good catalytic activity for a broad substrate scope including the aliphatic and aromatic olefins, affording the desired aldehydes in good yields. The catalyst could be reused several times without loss of activity under identical reaction conditions, and the Rh leaching was negligible after each cycle. More details are discussed in the article by Shi et al . on page 139 ‐ 143. Abstract : The back cover picture shows an efficient organic ligand‐free heterogeneous catalytic system for hydroformylation of olefins with simple Rh particles as the catalyst. The Rh black catalyst showed good catalytic activity for a broad substrate scope including the aliphatic and aromatic olefins, affording the desired aldehydes in good yields. The catalyst could be reused several times without loss of activity under identical reaction conditions, and the Rh leaching was negligible after each cycle. More details are discussed in the article by Shi et al . on page 139 ‐ 143.